Learning Styles of Engineering Students - Tulsi, P. K.; Poonia, M. P.; Priya, Anu (Journal of Engineering Education Transformations, 2016)
The study aimed at determining the learning styles of students pursuing master’s degree programmes in engineering. Index of Learning Style was administered to 175 students. The findings reveal that there exist differences in learning styles of students pursuing master’s degree in computer science and engineering, civil engineering, electrical engineering, electronics and communication engineering and mechanical engineering.Majority of the students of various branches except of mechanical engineering prefer active, sensing, visual and sequential learning styles but very few of them have strong preference for a particular learning style.